Penerapan Pendekatan Matematika Realistik untuk Meningkatkan Kemampuan Numerasi dalam Kurikulum Merdeka - Uswatun Hasanah; Wawan Shokib Rondli (ILUMINASI: Journal of Research in Education, 2023)
APPLICATION OF A REALISTIC MATHEMATICAL APPROACH TO IMPROVENUMERACY SKILLS IN THE INDEPENDENT CURRICULUM. Lack of numeracy skills results in low learning outcomes so that learning must be done with a real approach. The Realistic Mathematical Approach can be used as a solution in learning mathematics. This study aims to improve numeracy skills IV at SD 3 Adiwarno regarding the material of cheerful fractions using a realistic mathematical approach. The method used is qualitative and quantitative methods with a sample of 21 students. The research instruments are observation, interviews, documentation and tests. Data were analyzed with statistical data techniques. Based on the analysis of the results of the study, it showed that there was an effect of a realistic mathematical approach on students' numeracy skills, with an increase in pre-cycle 38.09% in cycle I by 66.67% to 85.71%. The suggestion of this research is that educators can apply a realistic mathematical approach by adjusting the material and characteristics of students